Photocatalytic enhancement of hydrogen production in water splitting under simulated solar light by band gap engineering and localized surface plasmon resonance of ZnxCd1-xS nanowires decorated by Au nanoparticles. (January 2020) - Chen, Yu-Cheng; Huang, Yu-Sheng; Huang, Han; Su, Po-Jui; Perng, Tsong-Pyng; Chen, Lih-Juann
Abstract: Excellent photocatalytic properties for hydrogen production in water splitting under simulated solar light (with AM1.5G filter) with Au nanoparticles (NPs)/Znx Cd1-x S nanowires (NWs) have been demonstrated. The Znx Cd1-x S NWs photocatalyst shows much higher photocatalytic activity for H2 -production than ZnS and CdS NWs with Na2 S and Na2 SO3 as sacrificial reagents. The high photocatalytic H2 -production activity, as high as 57.07 mmol g −1 h −1, is attributed to appropriate band gap width and suitable conduction band edge potential of the Znx Cd1-x S NWs. The H2 -production efficiency was further significantly enhanced to 96.04 mmol g −1 h −1 by decorating Znx Cd1-x S NWs with appropriate size and distribution of Au NPs to induce localized surface plasmon resonances (LSPR) in visible and near infrared region. The work represents significant advance with a totally green and novel approach of enhancing H2 -production efficiency in water splitting under simulated solar light (with AM1.5G filter). Graphical abstract: Image 1 Highlights: Band gap engineering of Znx Cd1-x S nanowires to enhance photocatalytic hydrogen production in water splitting. Enhancement of photocatalytic hydrogen production by localized surface plasmon resonance of Znx Cd1-x S nanowires decorated by Au nanoparticles. The excellent performance points to an effective strategy for the design and development of nanomaterials for photocatalytic applications.